2018
DOI: 10.1038/s41598-018-27997-8
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid computational approach for efficient Alzheimer’s disease classification based on heterogeneous data

Abstract: There is currently a lack of an efficient, objective and systemic approach towards the classification of Alzheimer’s disease (AD), due to its complex etiology and pathogenesis. As AD is inherently dynamic, it is also not clear how the relationships among AD indicators vary over time. To address these issues, we propose a hybrid computational approach for AD classification and evaluate it on the heterogeneous longitudinal AIBL dataset. Specifically, using clinical dementia rating as an index of AD severity, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 46 publications
(39 reference statements)
9
53
0
Order By: Relevance
“…Furthermore, both DRM and IRM scores exhibited very similar trend information, as the Spearman rank-correlation analysis between both scores produced an almost perfect relationship ( = 0.94, with negligible p-value). To some extent, this is also consistent with our previous analysis (albeit using a different dataset) that showed a probabilistic causal relationship between immediate and delayed recall memory scores 34 .…”
Section: High-dimensional Fc Analysis Can Detect Brain-wide Communicasupporting
confidence: 92%
“…Furthermore, both DRM and IRM scores exhibited very similar trend information, as the Spearman rank-correlation analysis between both scores produced an almost perfect relationship ( = 0.94, with negligible p-value). To some extent, this is also consistent with our previous analysis (albeit using a different dataset) that showed a probabilistic causal relationship between immediate and delayed recall memory scores 34 .…”
Section: High-dimensional Fc Analysis Can Detect Brain-wide Communicasupporting
confidence: 92%
“…In contrast to MMSE, MoCA, and ADAS13, the FAQ is not used in everyday clinical routine (Ritter et al, 2015). However, its relevance for determining impairment in everyday functioning and ensuring accurate early diagnosis of AD has been well-documented (Devanand et al, 2008, Ding et al, 2018, Ritter et al, 2015). For instance, studies found the use of FAQ can significantly contribute to discerning MCI versus AD cases with MoCA scores overlapping in the MCI range (Trzepacz et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…While most of deep learning models show great performance in diagnostic classification, their interpretation remains an emerging field of research (Che, Purushotham, Khemani, & Liu, 2016). Other machine learning approaches for assisted diagnosis of cognitive impairment and dementia include linear regression (Agosta et al, 2012, Bauer et al, 2018, Koch et al, 2012), penalized regression (Wang, Liu, & Shen, 2018), Bayesian networks (Ding et al, 2018), hidden Markov models (Wang et al, 2014), and probabilistic multiple kernel learning (MKL) classifiers (Korolev et al, 2016, Youssofzadeh et al, 2017). Despite the common use of machine learning techniques for the disease diagnostics, controversy still exists regarding the effects of different combinations of explanatory variables, hyper-parameter tuning, sample size and class balance on the performance of predictive models (Du, Fu, & Calhoun, 2018, Finch & Schneider, 2007, Michie, Spiegelhalter, & Taylor, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the complexity of AD, data analytical approaches can holistically capture the relationship across multiple data features, for example, using probabilistic graphical modeling [30]. In particular, Bayesian network modeling, a specific type of directed acyclic graphical modeling of conditional dependences/probabilities (reflected as edges in a graph), is easy to use and interpret without too many assumptions [30,5] and Lifestyle Study of Ageing (AIBL), [16] made use of Bayesian network modeling to capture the probabilistic causal relationship between very different data types as diverse as age, genotype, cognitive and functional assessments, and coarse-grained (total volume) neuroimaging data.…”
Section: Data-driven and Ai Approachesmentioning
confidence: 99%